Sterilizing of Alphitobius diaperinus (Panzer, 1797) (Coleoptera: Tenebrionidae) irradiated in pupa stage - Valter Arthur (Brazilian Journal of Radiation Sciences, 2021)
Worldwide the loss of stored grain is a problem of economic order of importance, in view of the concern of the increased supply of food for a world population increasingly expanding. Associated with this fact, there is the problem of nutritional deficiency due to lack of protein, especially for the less privileged populations in the resources of a country. This lack could be met by adequate supply of grain produced, requiring for it, a system that provides optimum grain storage conditions in securing the quality until the time of consumption. The use of radiation in stored grain can solve the problem of the losses in these products, as it does not induce resistance of insects and leaves no toxic residue to the consumer, and is considered an effective and safe method. The aim of the experiment was to determine the sterilizing dose of ionizing radiation from cobalt-60 to Alphitobius diaperinus  (Panzer, 1797)(Coleoptera: Tenebrionidae) in peanuts irradiated in pupa stage. The experiment was conducted in the laboratory of Radiobiology and Environment of the Center for Nuclear Energy in Agriculture - CENA / USP., Piracicaba, SP, Brazil. Peanuts samples infested with pupae of A. diaperinus were utilized in the experiment that consisted of 8 treatments with 5 repetitions. Each repetition consisted of 20 pupae a total of 100 individuals per treatment. Were irradiated with doses of 0 (control), 25, 50, 75, 100, 125, 150 and 175 Gy, in a source of cobalt-60, Gammacell-220 type, with a rate dose of 381Gy / h. The experiment was conducted in a room with temperatures of 25 ± 5 ° C and relative humidity of 70 ± 5%. After of irradiation process was evaluated of the number of emerged adult insects in each repetition in the treatments. The results show that the sterilizing dose in F1 generation was 125 Gy and the pupa lethal dose 150 Gy. The dose of 150 Gy of gamma radiation can be used as phytosanitary treatment to control of   immature stages of A. diaperinus infested peanuts.